2014
DOI: 10.1099/ijs.0.058412-0
|View full text |Cite
|
Sign up to set email alerts
|

Paenalcaligenes suwonensis sp. nov., isolated from spent mushroom compost

Abstract: A bacterial strain, ABC02-12 T , was isolated from spent mushroom compost, a waste product of button mushroom cultivation. Cells of the strain were Gram-stain-negative, catalase-and oxidasepositive, non-spore-forming, aerobic flagellated rods. Paenalcaligenes hermetiae KBL009 T . The quinone system was ubiquinone Q-8 with minor amounts of Q-7. The major fatty acids (.5 % of total fatty acids) were C 16 : 0 , C 16 : 1 v6c and/or C 16 : 1 v7c (summed feature 3), C 18 : 1 v7c and/or C 18 : 1 v6c (summed feature 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
(23 reference statements)
0
11
0
2
Order By: Relevance
“…It was first described in 2010 on the basis of a strain isolated from the blood culture of an 85-year-old man (1). Currently, three species are recognized: P. hominis (1), P. hermetiae (2), and P. suwonensis (3). Due to the lack of whole-genome sequences in the NCBI database from any members of the genus Paenalcaligenes , we sequenced a P. hominis isolate.…”
Section: Genome Announcementmentioning
confidence: 99%
“…It was first described in 2010 on the basis of a strain isolated from the blood culture of an 85-year-old man (1). Currently, three species are recognized: P. hominis (1), P. hermetiae (2), and P. suwonensis (3). Due to the lack of whole-genome sequences in the NCBI database from any members of the genus Paenalcaligenes , we sequenced a P. hominis isolate.…”
Section: Genome Announcementmentioning
confidence: 99%
“…However, 16S rRNA gene sequencing performed by our group indicated that the isolate was more closely related to another member of the Alcaligenaceae family, Paenalcaligenes suwonensis. Paenalcaligenes species have been isolated from both the environment (1) and patients (2, 3), and only one genome has been sequenced for the genus to date (P. hominis).…”
Section: Announcementmentioning
confidence: 96%
“…The type species Paenalcaligenes hominis was isolated from human blood [4]. Two additional species were then proposed: Paenalcaligenes hermetiae , isolated from the larval gut of Hermetia illucens [5], and Paenalcaligenes suwonensis , isolated from spent mushroom compost [6]. So far, species within the genus are Gram-stain negative, short rods, catalase- and oxidase-positive, and mainly showing an aerobic respiratory metabolism.…”
Section: Isolation and Ecologymentioning
confidence: 99%